ANÁLISIS DE LA INCORPORACIÓN FISCAL DE UNA MICROEMPRESA QUE SE ENCUENTRA EN LA INFORMALIDAD - Sánchez, Lizbeth Ochoa; de la Cruz, Arturo Aguilar; Magaña, Sergio Alfonso Tosca (IJRDO - Journal of Business Management, 2021)
The situation caused by the lack of tax culture in people who perform various activities considered economic for tax regulation, brings with it a problem known as tax evasion, which in most cases occurs not only by the omission of obligations, but by the ignorance of such obligations, which in most cases is due to not knowing that certain economic activity brings with it obligations that must be fulfilled before the relevant tax authority. One of the main taxpayers in this group are micro-entrepreneurs or micro-companies that operate informally for the tax authorities, causing such evasion. The analysis of the reasons why many micro-enterprises are not in the formality, allows to know, what action should be taken, in order to instruct the micro-entrepreneurs the tax culture, as a way of life in their businesses, or enterprises, etc.